2013
DOI: 10.1097/ccm.0b013e31829791a2
|View full text |Cite
|
Sign up to set email alerts
|

Character and Temporal Evolution of Apoptosis in Acetaminophen-Induced Acute Liver Failure*

Abstract: Objective To evaluate the role of hepatocellular and extrahepatic apoptosis during the evolution of Acetaminophen-induced acute liver failure (AALF). Design & Setting A prospective observational study in two tertiary liver transplant units. Patients 88 patients with AALF were recruited. Control groups included patients with non-AALF (n=13), non-hepatic multi-organ failure (MOF, n=28), chronic liver disease (CLD, n=19) and healthy controls (HC, n=11). Measurements Total and caspase-cleaved cytokeratin 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 35 publications
3
37
0
Order By: Relevance
“…In addition, they showed a negative gradient of M30 from the portal to the hepatic vein at later time points, suggesting that M30 could not come from the liver. This conclusion was supported by the absence of apoptotic cell death in the explant (10). These data are the first to provide evidence for caspase activation in extrahepatic tissue during AALF.…”
supporting
confidence: 62%
See 3 more Smart Citations
“…In addition, they showed a negative gradient of M30 from the portal to the hepatic vein at later time points, suggesting that M30 could not come from the liver. This conclusion was supported by the absence of apoptotic cell death in the explant (10). These data are the first to provide evidence for caspase activation in extrahepatic tissue during AALF.…”
supporting
confidence: 62%
“…Nevertheless, consistent with previous reports (11,12), M30 levels were highest at the time of admission, suggesting that hepatocellular apoptosis occurs in the early phase of acetaminophen hepatotoxicity. Although previous work in our laboratory failed to detect active caspase-3 in plasma from acetaminophen overdose patients with liver injury (13), Possamai et al (10) in their study pointed out that these patients may have presented too late to detect markers of apoptosis. However, this is not very likely.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Animal studies had previously suggested necrotic death due to depletion of intracellular ATP to be the primary mechanism, but a more recent study demonstrated (Bunchorntavakul and Reddy 2013)] 1 3 increased serum markers of apoptosis (caspase cleaved CK-18, also referred to as M30) in patients with acetaminophen-induced ALF, compared to matched controls. Additionally, M30 levels on admission predicted progression to liver transplantation or death with a sensitivity of 89 % and a specificity of 69 %, suggesting a critical role of apoptosis in the progression of ALF in acetaminophen overdose (Possamai et al 2013). …”
Section: Pathophysiologymentioning
confidence: 99%